Reversible dehydrogenation and rehydrogenation of cyclohexane and methylcyclohexane by single-site platinum catalyst - Chen, Luning; Verma, Pragya; Hou, Kaipeng; Qi, Zhiyuan; Zhang, Shuchen; Liu, Yi-Sheng; Guo, Jinghua; Stavila, Vitalie; Allendorf, Mark D.; Zheng, Lansun; Salmeron, Miquel; Prendergast, David; et al. (Nature communications, 2022)
Developing highly efficient and reversible hydrogenation-dehydrogenation catalysts shows great promise for hydrogen storage technologies with highly desirable economic and ecological benefits. Herein, we show that reaction sites consisting of single Pt atoms and neighboring oxygen vacancies (V O ) can be prepared on CeO 2 (Pt 1 /CeO 2 ) with unique catalytic properties for the reversible dehydrogenation and rehydrogenation of large molecules such as cyclohexane and methylcyclohexane. Specifically, we find that the dehydrogenation rate of cyclohexane and methylcyclohexane on such sites can reach values above 32,000 mol H2 mol Pt −1 h −1 , which is 309 times higher than that of conventional supported Pt nanoparticles. Combining of DRIFTS, AP-XPS, EXAFS, and DFT calculations, we show that the Pt 1 /CeO 2 catalyst exhibits a super-synergistic effect between the catalytic Pt atom and its support, involving redox coupling between Pt and Ce ions, enabling adsorption, activation and reaction of large molecules with sufficient versatility to drive abstraction/addition of hydrogen without requiring multiple reaction sites. Developing highly efficient and reversible hydrogenation-dehydrogenation catalysts shows great promise for hydrogen storage technologies. Here the authors develop a highly efficient and reversible de/rehydrogenation single-site platinum catalyst which exhibits great promise for hydrogen storage technologies with cyclic alkanes/aromatics as liquid organic hydrogen carriers.